ZELab: planning a living lab to educate modern engineering professionals - Felgueiras, Manuel Carlos (2019)
Buildings are now complex systems that traditionally have been studied in an isolated mode, seeking to respond to a specific need and dealing with a restricted set of variables. The targets established for energy efficient buildings and energy sustainability imply that these new systems are now more comprehensive and combine various independent systems. This new topology requires a new kind of engineering professionals trained in a more integrative and collaborative way. These new engineering professionals need to have not only expertise in a specific area, but also more comprehensive proficiencies that allow them to understand how to integrate their particular project into a wider functional system, and to communicate with experts from different areas. This paper addresses some challenges and issues posed to Higher Education institutions on the educational paradigms of future engineering professionals and proposes the ZELab teaching / research space as an integrative educational tool.